RANCANG BANGUN SISTEM INFORMASI KEPENDUDUKAN DESA PARAKANLIMA BERBASIS WEB DENGAN MENGGUNAKAN METODE WATERFALL - Novita, Novitasari (Jurnal RESTIKOM : Riset Teknik Informatika dan Komputer, 2019)
ABSTRACT Data management of population of Desa parakanlima in Cikembar district in Sukabumi regency has been performed in old fashion. Data is written on the paper and stored in the filling cabinet. This research develop an information system to manage the data such that it can be easier and more accurate. This system was developed with the waterfall method. System evaluation on the aspect of display by the user shows an average value of 78.38% which means the system is good. The results of software testing indicate that the functions in the Country Information System of Tulang Bawang Village have been running well according to the requirements. The conclusion is that this system is feasible to be used to assist village staff in managing population data. Keywords: Information System, Village, Waterfall